The Ballad of Karla Faye Tucker. By Mark Beaver. Jackson, Mississippi: University Press of Mississippi, 2023. 213 pp. $ 22.00 paper - McMichael, Mandy (Church history, 2024)
The Ballad of Karla Faye Tucker. By Mark Beaver. Jackson, Mississippi: University Press of Mississippi, 2023. 213 pp. $ 22.00 paper. - Volume 93 Issue 3.